Cuba in the American Imagination : Metaphor and the Imperial Ethos - Perez, Louis A., Jr., 1943- (Book collections on Project MUSE., 2008)
For more than two hundred often turbulent years, Americans have imagined and described Cuba and its relationship to the United States by conjuring up a variety of striking images--Cuba as a woman, a neighbor, a ripe fruit, a child learning to ride a bicycle. One of the foremost historians of Cuba, Louis A. Perez Jr. offers a revealing history of these metaphorical and depictive motifs and discovers the powerful motives behind such characterizations of the island.